Mature Cystic Teratoma of the Ovary; Clinicopathological Evaluation of 143 Cases in our Series, 5 Years Experience - Kazanci, Ferah; Ogut, Betul; Yapar, Dilek; Erdem, Ozlem; Onan, M. Anil (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: Mature cystic teratoma, also known as a dermoid cyst, is the most common germ cell tumor of the ovary. In this retrospective study, it is aimed to evaluate clinicopathological findings of the patients who were operated on due to the preliminary diagnosis of dermoid cyst. STUDY DESIGN: Between May 2013 and May 2018, the findings of a total of 143 patients who were operated on with a preliminary diagnosis of dermoid cyst in our institution were analyzed retrospectively. In addition to demographic characteristics such as age, parity number and tumor size, lateralization, preoperative tumor markers, surgical procedure, presence of other pathological findings, and the rate of malignant transformation were analyzed. RESULTS: The median age of patients was 35.4 years and the ratio of nulliparous, primiparous, and multiparous patients was 46.9%, 25.2%, and 28%, respectively. The median tumor diameter was 6.7 cm, 50.3% of which were right-sided, 46.9% were left-sided and the remaining 2.8% were bilateral. Intraoperative torsion was found in 15 (10.5%) cases. The treatment consisted of 60.1% cystectomy by laparoscopy, 3.5% unilateral salpingo-oophorectomy by laparoscopy, 9.8% unilateral salpingo-oophorectomy by laparotomy, while the rate of 16.1% cases underwent hysterectomy with bilateral salpingo-oophorectomy by laparotomy, 10.5% of the cases, cysts were excised during cesarean section. As the final pathology report revealed, of 143 patients, immature teratoma was observed in five cases (3.5%), in one of them (0.7%) mixed germ cell tumor and in three of them (2.1%) borderline mucinous cancer, squamous cell carcinoma, and carcinoid tumor on mature cystic teratoma base were observed. CONCLUSION: Torsion is the most common complication with mature cystic teratoma. The size of the tumor is an important prognostic factor in terms of the malignant transformation of teratoma. Fertility sparing surgery with a minimally invasive surgical approach is available for fertility patients diagnosed with Mature cystic teratoma.